Development framework towards center of excellence for the bachelor of science in accountancy program of the Mariano Marcos State University, Philippines - Corpuz, Lorelei joy A. (Divine Word College of Laoag : [s.n.], 2020)
The study formulated and validated a Development Framework towards Center of Excellence for the BS in Accountancy Program of the Mariano Marcos State University based on the results of the benchmarking process involving the schools identified as Center of Excellence and Center of Development institutions in Accountancy in the Philippines. The research and development (R and D) methodology with three major stages, namely: planning, development and validation was used. Benchmarking was conducted in institutions identified by the Commission on Higher Education as Center of Excellence (COE) and Center of Development (COD) in Accountancy, namely: De La Salle University in Manila for the COE institution; and University of San Jose - Recoletos in Cebu City and University of Mindanao in Davao City for the COD institutions, respectively. Three groups of respondents were involved in this study. The first two groups of respondents include the Faculty Members, Department/Unit Heads of the Accountancy Program and School Administrators (e.g. Dean, Vice-President for Academic Affairs, Research Director, Extension Director, Research and Extension Focal Persons of the college, Librarian, Director for Physical Plant and Facilities, Registrar, Alumni Focal Person, Student Affairs Coordinator) of benchmarking partners and the benchmarking school. They were chosen purposively wherein for the faculty, only those who have been involved in the Accountancy Program for at least a year were included. Whereas, for the Department/Unit Head the criterion was at least a year as a Department/Unit Head and for the School Administrators was at least a year as a School Administrator. The third group of respondents in the study were the panel of experts who validated the Development Framework. The data were gathered using a questionnaire, unstructured interviews with some key informants and documentary analysis. Frequency count and percentage were used to describe the problems encountered by the benchmarking school, the Mariano Marcos State University. Weighted mean was used to analyze the status of the benchmarking school and the institutions of Center of Excellence and Centers of Development in Accountancy. Further, the best practices of the COE and COD institutions were analyzed and interpreted qualitatively. Likewise, weighted mean was also used in determining the validity of the Development Framework. The significant findings of the study were as follows: The ratings given by the respondents of the benchmarking school fell short as compared to the ratings given by respondents of COE/CODs in the areas of Faculty Qualifications, Adequacy and Quality of Physical and Educational Resources, Involvement in Graduate Education, Scale, Passing Rate in the CPA Licensure Examination and Impact of Graduates, Scholarly Work and Publication Output, and Leadership Role Played in the Field. There are various exemplary practices of the COE and COD institutions along Instructional Quality, Research, Extension, Outreach and Linkages, and Institutional Qualifications that could be adapted by the BS Accountancy Program of MMSU to facilitate its compliance to CMO#10 s. 2007. The respondents of the benchmarking school perceived that the following problems frequently surface and/or encountered by the institution in the implementation of the BS Accountancy Program. They are arranged according to degree of complexity: lack of retention policy; emotional non-readiness of students; lack of students' commitment; shallow knowledge of students in accounting; poor ventilation of classrooms and laboratory rooms; and big class size. Further, the main obstacles or challenges in improving the pass and sit rates in the CPA Licensure Examination of the benchmarking school are: unfinished topics in the undergraduate; faculty competencies; and, changes in standards, tax laws and provisions that create gaps between those discussed in the lower levels of the undergraduate and those that are included in the CPA Licensure Examination. Meanwhile, emotional non- readiness and financial conditions of the graduates were identified as main impediments or deterrents that keep accounting graduates from eventually sitting for the CPA Licensure Examination. The panel of experts' evaluation of the essential elements of the Development Framework towards Center of Excellence for the BS in Accountancy Program of the Mariano Marcos State University based on the criteria showed their very strong agreement described as very strongly agree. The mean scores show that the Development Framework towards Center of Excellence for the BS Accountancy Program of the Mariano Marcos State University is very highly valid, hence, it can be used by the School Administrators to enhance the Program. The study concludes that there are strengths and weaknesses of the Bachelor of Science in Accountancy Program of the Mariano Marcos State University with regards to its compliance to CMO#10 s. 2007. The use of benchmarking process is very relevant and valid in determining the best practices which could be adapted by MMSU towards its goal of Center of Excellence for the Accountancy Program. The BS Accountancy Program has its own share of challenges in varying degrees along Students, Faculty, Adequacy of Physical Facilities, Research, Extension, Outreach and Linkages; and Institutional Qualifications. The Development Framework is very highly valid, hence, the benchmarking school can use the Framework to address the identified weaknesses and provide better quality Accountancy Education and ultimately towards its goal of Center of Excellence for the BS in Accountancy Program. In the light of the above-mentioned findings and conclusions, the following recommendations are offered: a copy of the Development Framework should be provided to the Dean and Department Chair/Program Head to thoroughly study and to seek the approval of the higher authorities of the university for implementation. The framework will be disseminated to the faculty members, parents, heads of agencies/industries, heads of local government units, heads of professional organizations and other stakeholders for their cooperation and support towards a more effective implementation of the programs and activities. An assessment of the impact of the Development Framework should be conducted by the Commission on Higher Education officials immediately after the implementation of the framework to determine its effectiveness and efficiency in meeting its goals and objectives and in improving the quality of Accounting education at Mariano Marcos State University.
Bibliography: pages 510-519.
CHED-La Union
Keywords: Accounting -- Study and teaching; Accounting -- Curricula